2017
DOI: 10.1002/ase.1719
|View full text |Cite
|
Sign up to set email alerts
|

Validation of clay modeling as a learning tool for the periventricular structures of the human brain

Abstract: Visualizing anatomical structures and functional processes in three dimensions (3D) are important skills for medical students. However, contemplating 3D structures mentally and interpreting biomedical images can be challenging. This study examines the impact of a new pedagogical approach to teaching neuroanatomy, specifically how building a 3D-model from oil-based modeling clay affects learners' understanding of periventricular structures of the brain among undergraduate medical students in Colombia. Students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 37 publications
0
40
0
1
Order By: Relevance
“…Because each individual has a preferred mode of learning (Kim et al, 2016;Ojeh et al, 2017), it is important to provide students with a variety of teaching methodologies tailored to differences in learning preferences (Anbarasi et al, 2015). Examples include plastinated specimens (Riederer, 2014), clay-based models (Kooloos et al, 2014;Akle et al, 2018) and computer-based learning resources (Bryner et al, 2008;Mayfield et al, 2013;Trelease, 2016), such as digital image libraries for clinically oriented anatomy teaching (Elizondo-Omaña et al, 2005;Pujol et al, 2016) and virtual 3D models (Nicholson et al, 2006;Keedy et al, 2011;Cui et al, 2016). While computer-based 3D models act as good supplementary study aids (Wilson et al, 2019) and present a user with an interactive and dynamic 3D vision of difficult anatomical structures (Petersson et al, 2009;Pujol et al, 2016), they are limited by their image resolution, the size of the monitor and more importantly, the lack of haptic feedback (Wainman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Because each individual has a preferred mode of learning (Kim et al, 2016;Ojeh et al, 2017), it is important to provide students with a variety of teaching methodologies tailored to differences in learning preferences (Anbarasi et al, 2015). Examples include plastinated specimens (Riederer, 2014), clay-based models (Kooloos et al, 2014;Akle et al, 2018) and computer-based learning resources (Bryner et al, 2008;Mayfield et al, 2013;Trelease, 2016), such as digital image libraries for clinically oriented anatomy teaching (Elizondo-Omaña et al, 2005;Pujol et al, 2016) and virtual 3D models (Nicholson et al, 2006;Keedy et al, 2011;Cui et al, 2016). While computer-based 3D models act as good supplementary study aids (Wilson et al, 2019) and present a user with an interactive and dynamic 3D vision of difficult anatomical structures (Petersson et al, 2009;Pujol et al, 2016), they are limited by their image resolution, the size of the monitor and more importantly, the lack of haptic feedback (Wainman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Given that it is often said that Millennials prefer to using state-ofthe-art technologies (e.g., Strauss and Howe, 2000;Meriac et al, 2010;Twenge et al, 2014), an unexpected finding that emerged from the literature was that physical models may be more beneficial than 3D virtual models when learning anatomy (Khot et al, 2013;Pawlina and Drake, 2013;Preece et al, 2013). Indeed, the clay models described by Estevez et al (2010) and Akle et al (2017) seemed to be particularly successful. Limitations on the use of physical models relate to costs (the price varying according to size and materials, for example) and to the possibility of damage caused during their manipulation by the students (Fredieu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, students who initially accessed the 3D online resources scored significantly better than those who initially were provided with just two-dimensional (2D) resources (P < 0.01). Akle et al (2017) and Estevez et al (2010) showed the efficacy of 3D clay models in neuroanatomy education. Quiz scores of students that constructed models were significantly higher than those who were taught in a more traditional manner (2D) (P < 0.05).…”
Section: Primary Outcomementioning
confidence: 99%
“…Además, en esta investigación los estudiantes de obstetricia describen que la actividad facilitó su aprendizaje, esto puede deberse al desarrollo de habilidades espaciales (Huk et al, 2006) señalando que las actividades basadas en construcción de modelos anatómicos 3-D promueven el aprendizaje, elemento que se podría relacionar si consideramos que los modelos 3-D favorecen el aprendizaje anatómico generando un puente eficaz entre las estructuras 2-D y 3-D (Lizana et al). Estudios similares utilizando arcilla para la construcción de modelos anatómicos muestran un aumento significativo en el aprendizaje de los estudiantes de medicina, resultando ser una actividad eficaz para la enseñanza y aprendizaje de estructuras anatómicas en cortes transversales (Oh et al, 2009), también la comprensión de estructuras perivetriculares del cerebro ha sido significativamente mejorada utilizando la construcción de modelos de arcilla con estudiantes de medicina (Akle et al, 2017). Otros estudios realizados con estudiantes de obstetricia demuestran que una intervención de modelamientos anatómicos de arcilla de la zona pélvica durante el programa de clases presentan una eficacia significativa para el aprendizaje de los estudiantes (Myers et al, 2001;Schmidt et al, 2017).…”
Section: Discussionunclassified